PENGARUH PERSEPSI GAYA KEPEMIMPINAN SERVANT LEADERSHIP DAN TIPE KEPRIBADIAN BIG FIVE PERSONALITY TERHADAP STRES KERJA (STUDI EMPIRIK PADA WARTAWAN INVESTOR DAILY DAN KORAN SINDO) - , Euis Rita Hartati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Journalist is one of the professions with high stress levels. The cause, among others, is the demand from the editors to produce an exclusive story in high degree of accuracy. Journalists, especially those who are working for daily print media (newspaper), also have to deal with the pressure of deadline every day. However, stress doesn't always means something negative, as for some people stress can become a driving force to increase the motivation and the inspiration to work harder. Therefore although considered to have high levels of stress, a lot of people are sticking with the profession as a journalist. Every person gives a different reaction in response to the same stress. The stress perception of each person is influenced by many factors, such as the perception to the leadership style in the organization and the characteristic of respective individual personality. The leadership style of serving (Servant Leadership) initiated by Robert K. Greenleaf in his book titled The Servant as Leader published in 1970 has become a new revolution in the concept of leadership and is considered to keep relevant up to now. This study aims to find out the correlation between the perception of the leadership style of serving (Servant Leadership) applied by the chief editors and the working stress suffered by the journalists, also to determine whether the personality types, the big five of Extroversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to Experience, affect the working stress to the journalists. The study was conducted by distributing questionnaires to 95 journalists from two newspapers in Jakarta namely Investor Daily and Koran Sindo. The result of the study shows negative correlation between the leadership style of serving (Servant Leadership) applied by the chief editors and the working stress of the journalists. In the meantime, among the five personality types, the Neuroticism and Agreeableness shows positive correlation to the stress, while the Extroversion, the Conscientiousness, and the Openness to Experience show negative correlation to the stress.